HUBUNGAN FAKTOR KELUARGA DENGAN KEKAMBUHAN PADA KLIEN SKIZOFRENIA DI POLIKLINIK RUMAH SAKIT JIWA PROF. DR. HB. SA’ANIN PADANG - Yudistira Afconneri; Khatijah Lim; Ira Erwina (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2019)
The national prevalence of severe mental disorders in Indonesia is 1.7 per mile and 70% of them are schizophrenia. The inability to control symptoms can cause recurrence in schizophrenic clients. The purpose of this study was to determine the relationship of family factors with the relapse of schizophrenic clients at Prof. Dr. HB. Sa’anin Padang. This type of research was descriptive correlative with a cross sectional approach with the number of respondents 173 people schizophrenia clients and families at Prof. RS Polyclinic. HB. Sa’anin Padang. The sampling technique is convinience sampling. The study was conducted from April to June 2016. Data collection was carried out using a questionnaire. The results showed that there was a significant relationship between family support and caregiver burden with relapse of schizophrenic clients (p <0,05). The results of this study are expected to be an input for nurses and related agencies to prevent the relapse of schizophrenia clients by providing an understanding of the importance of family support and forming a supportive group of schizophrenic client families. Keywords : Family, relapse, schizophrenia